THE PROPERTIES KRAFT PULP SENGON WOOD (Paraserianthes falcataria):Differences Of Cooking Liquor Concentration and Bleaching Sequence - Widya Fatriasari; Lucky Risanto (Pusbindiklat - LIPI, 2011)
The research was to investigate the difference effect of cooking liquor concentration and bleaching sequence on the properties Kraft pulp sengon wood (Paraserianthes falcataria). The Kraft pulp conditions were alkalinity (16 and 20%) and sulfi dity (20 and 25%). The maximum pulping temperature was 170°C for 4 hours, Liquor to wood ratio of 4:1 and 100 gram OD. Pulp bleaching sequences were P1 DEP2 and D1ED2P. Utilization of selected Kraft pulping was effective enough for dissolving lignin. The highest and the lowest lignin decreasing were 90% and 61% respectively. The increasing effect of alkali concentration was more dominant than its sulfi dity on the pulp delignifi cation selectivity. Generally, the optimum Kraft pulping conditions were alkalinity 20% and sulfi dity 25%. The sequence bleaching difference of the selected pulp tended on the decreasing of kappa number and pulp yield. The fi rst pulp bleaching method (P1EDP2) was relatively better than the second method (D1ED2P)